(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Using return on assets as a mediator, the purpose of this study is to determine the nature of the connection that exists between environmentally friendly product innovation and the value of a company. Utilizing the purposive sampling strategy is the method that is utilised for the selection of samples. Three hundred and thirty-two firm-year observations that were included in the Stock Exchange throughout the period of 2018-2023 were used to collect the samples. The Partial Least Square (PLS) test, which is carried out using WarpPLS 5.0, is utilised in the process of testing the hypothesis. In the first place, the findings of the study demonstrated that there is a considerable positive association between business value and green product innovation, as well as return on assets. Second, there is a considerable positive association between return on assets and the innovation of environmentally friendly products. Third, the return on assets has the potential to act as a partial mediator in the connection between environmentally friendly product innovations and the value of the company.